General relativity : a geometric approach - Ludvigsen, Malcolm, 1946- (Cambridge University Press, 1999)
A clear, concise and modern textbook introducing the theory of general relativity for final-year undergraduate maths or physics students. The emphasis is on the geometric structure of spacetime rather than the traditional coordinate-dependent approach. Exercises are provided (with solutions and hints) and key ideas are illustrated with worked examples.